ROBOTIC PROCESS AUTOMATION TECHNOLOGY IN SUPPLY CHAIN MANAGEMENT practical applications for... simplifying workflows. - Galińska, Barbara (PRODUCTIVITY PRESS, 2025)
This book analyses and presents the application of Robotic Process Automation technology (RPA) in supply chain management. It chronologically describes supply chain issues (definition and features, schema, management aspects, problems) and trends of Industry 4.0 solutions in supply chain management.